PENGARUH KUALITAS PELAYANAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA STARBOX BARBERSHOP KOTA BATAM - Gui, Shellen; Simanjuntak, Jontro (SCIENTIA JOURNAL, 2019)
Along with the development of the times and the increasing level of society, the lifestyle is also growing. Appearance is one that is considered by both men and women. Because it opened a man only salon known as Barbershop. This study aims to determine the effect of service quality and customer satisfaction on customer loyalty at the Batam City Starbox Barbershop. The sample of this study was 109 people with a population of all Starbox Barbershop customers in batam. Analysis of data techniques using regression analysis. With the result od testing, the Determination coefficien (R 2 ) is 56.6%. the result of the T test show the value of the t value of service quality variable is 3.780 from the customers statisfaction variable of 4.152 with the value of t table 1.982. both variables are greater than t table and can be stated – each variable has a significant influence on customer loyalty. So it can be concluded that the result of variable analysis of service quality and customer loyalty on Starbox Barbershop in Batam City.